A Second-Order Nonlinear Problem with Two-Point and Integral Boundary Conditions - Brykalov, S. A. (Georgian mathematical journal, 1994)
The paper gives sufficient conditions for the existence and nonuniqueness of monotone solutions of a nonlinear ordinary differential equation of the second order subject to two nonlinear boundary conditions one of which is two-point and the other is integral. The proof is based on an existence result for a problem with functional boundary conditions obtained by the author in [Brykalov, Differential Equations 27: 1415-1420, 1991].